Taxing bitcoin transactions under Polish tax law - Patryk Kowalski (Comparative Economic Research. Central and Eastern Europe, 2015)
Recent years have witnessed the emergence of digital currencies - digital representations of value which are transferred using IT technologies and used as a medium of exchange but are not recognised as official means of payment. Bitcoins are one of such currencies and their popularity in Europe and in Poland has been growing. Hence it is a good time to consider to what extent Polish law is prepared to face the phenomenon and what potential problems may arise from it for the judicial system. The main objective of the paper is to analyse Polish tax regulations in the context of bitcoin transactions, as broadly understood.
Keywords: 330; bitcoin; tax; transactions; polish tax law; virtual currency; digital currency; PIT; CIT; VAT; PCC; bitcoin